Modeling the efficiency of a Solar-Reflector Antenna used as a Safe Energy Alternatives: Calculations from Sudanese data - Bashir, Saad Osman (2011)
In this work, it was shown by calculations that crudeoil’s extinction is definite, and oil air-pollution is increasing significantly as a function of time (civilization). Hence, a parabloidal reflector antenna is suggested here to extract solar energy as a concentrated solar-induced heat. This heat could be used for electrical power plants, photovoltaic plants, industry,cooking, heating, and water-heating etc. Also, it was shown experimentally, at X-band, that a layer of wet sand on such a parabloidal reflector antennas can strongly degrade their overall efficiency. Experiment confirmed the theoretical picture of the dry dust layer producing a phase shift of the aperture field of the parabloidal reflector antenna. It was theoretically predicted, and confirmed experimentally, that a severe loss of signal would occur at X-band for a layer covering half the dish and with a thickness about 8 mm, to give near o 180 phase shift in the aperture. Obviously, this with a much lower thickness values will be applicable in the optical frequency band.